Generation of a bivalent dengue virus-like particle targeting DENV-1 and DENV-2 in Pichia pastoris - Kusumawardani, Shinta; Yusuf, Muhammad; Yosua, Yosua; Syafrudin, Elza Nurrachmanita; Baroroh, Umi; Nurainy, Neni; Subroto, Toto (Universitas Gadjah Mada, 2026)
Dengue remains a major global health concern, with current licensed vaccines offering variable protection across the four virus serotypes and posing safety considerations related to antibody-dependent enhancement (ADE). To contribute toward improved vaccine design, we developed a bivalent virus-like particle (VLP) targeting DENV-1 and DENV-2, the two most prevalent serotypes in Indonesia. Consensus envelope (CE) protein sequences from Indonesian DENV-1 and DENV-2 strains were codon-optimized and co-expressed in Pichia pastoris GS115 using the AOX1 promoter. The expressed proteins were solubilized from membrane fractions under denaturing conditions, purified via Ni2+-affinity chromatography, and subjected to urea gradient dialysis for VLP assembly. Transmission electron microscopy confirmed the formation of spherical VLPs. Western blot analysis confirmed expression and purification via anti-His detection, and supported antigenic integrity of the envelope proteins as recognized by anti-dengue E antibodies. The study demonstrates the feasibility of using P. pastoris for chimeric dengue VLP production based on regionally relevant strains. The findings support the development of serotype-focused VLP platforms as modular components in the development of future tetravalent dengue vaccines.